Great Britain & Reza Shah : the plunder of Iran, 1921-1941 - Majd, Mohammad Gholi, 1946- (University Press of Florida, 2001)
''A completely fresh interpretation of the 1921-1941 Pahlavi period. ... Majd has come upon a gold mine of information on this controversial period of Persian history. ... The details and freshness of the figures are explosive. ... Even more explosive are the land acquisitions materials and the information on the work of the Shah's secret police.